2011
DOI: 10.1007/s00894-011-1232-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematical comparison of DFT methods in reproducing the interaction energies of halide series with protein moieties

Abstract: A systematic theoretical investigation on the interaction energies of halogen-ionic bridges formed between halide ions and the polar H atoms bonded to N of protein moieties has been carried out by employing a variety of density functional methods. In this procedure, full geometry optimizations are performed at the Møller-Plesset second-order perturbation (MP2) level of theory in conjunction with the Dunning's augmented correlation-consistent basis set, aug-cc-pVDZ. Subsequently, two distinct basis sets, i.e. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 93 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Other benchmarking studies have demonstrated that B97-1 performs well in modeling van der Waals interactions containing a significant charge-transfer component. Some of the top performing functionals in this study have been shown to provide the smallest deviations in energy from higher-level calculations in modeling halogen bonds of small halocarbon molecules with neutral Lewis bases (B97-1, B98, PBE1PBE) as well as halide–protein complexes (B97-1, B98) …”
Section: Resultsmentioning
confidence: 98%
“…Other benchmarking studies have demonstrated that B97-1 performs well in modeling van der Waals interactions containing a significant charge-transfer component. Some of the top performing functionals in this study have been shown to provide the smallest deviations in energy from higher-level calculations in modeling halogen bonds of small halocarbon molecules with neutral Lewis bases (B97-1, B98, PBE1PBE) as well as halide–protein complexes (B97-1, B98) …”
Section: Resultsmentioning
confidence: 98%